Lyrics and rhythm: a study of salsa music poetics - Becerra Mayorga, Witton; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2022)
Salsa has been widely developed as a musical style, as well as part of Spanish American culture, specifically from the Spanish Caribbean. The purpose of this book is to investigate the poetics of salsa music produced in New York City, and “presalsa” in particular, which is the name coined to the Cuban and Puerto Rican rhythms preceding and establishing the musical and poetic patterns of salsa music. The main issue elucidated here is how salsa and presalsa music take their poetic forms from the “décima espinela”, a 17th century Spanish poetic style, coupled with sounds from Bantu languages called “jitanjáforas”. Also, the purpose of this book is to study salsa and presalsa lyrics within the categories of “canción salsa relato”, “canción salsa poema”, and “canción salsa jitanjáfora”. The case study method is applied in this research to analyze the lyrics of salsa and presalsa music at three different levels – observation, interpretation and assertions. This methodology is a relevant aspect of the research in order to report specific lyrics which represent poetic patterns in these music styles. Complemented by cultural theory, each case study is described in depth with concepts that explain the development of this type of music in popular culture. In the first part, the approach to culture, popular culture, and popular music are fundamental, as they are the theoretical concepts that form the basis of this research. This contributes to the study of how the use of the “décima” originated from popular culture and reaches Puerto Rican and Cuban music and from there passes on to New York City. Popular culture and popular music also generate an approach to the use of “jitanjáforas” in the poetry of Nicolás Guillén and Luis Palés Matos and leads to the explanation of how it is manifested in salsa and in presalsa music as well. In addition to how the poetics of salsa and presalsa emerge, the case studies are used to understand the poetic configuration of salsa in the songs seen from the perspective of story, poem and jitanjáforas. The main outcome achieved in this dissertation is the complementary approach to salsa music by means of poetics. According to the literature review presented in this research, the most important studies in the area of popular music and salsa are related to ethnomusicology. Consequently, this book goes beyond this and proposes salsa and presalsa lyrics as a literary style.